Context-specific and context-invariant computations of interval timing - Pourmohammadi, Ahmad; Sanayei, Mehdi (Frontiers in Neuroscience, 2023)
An accurate sense of time is crucial in flexible sensorimotor control and other cognitive functions. However, it remains unknown how multiple timing computations in different contexts interact to shape our behavior. We asked humans to perform timing tasks that differed in the sensorimotor domain (sensory timing vs. motor timing) and effector (hand vs. saccadic eye movement). To understand how these different behavioral contexts contribute to timing behavior, we applied a threestage Bayesian model to behavioral data. We found that these behavioral contexts affect different stages of computations about time. The motor response computations in our timing tasks are only affected by the mode of response. Moreover, our results indicated that the mode of response also affects computations related to measuring and sensing time. The sensorimotor domain only has effects on the measurement stage of interval timing. These findings suggest that both context-specific and context-invariant computations contribute to shaping our timing behavior.